Effect of weeding regime on the performance of boro rice cultivars: Effect of weeding on boro rice (Journal of the Bangladesh Agricultural University, 2019)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from December 2016 to May 2017 to investigate the effect of weeding regime on the performance of boro rice cultivars. The experiment comprised of two factors, Factor A-  Rice cultivars: BRRI dhan28, BRRI dhan29, and BRRI dhan74, Factor B: Methods of weeding- no weeding, two hand weedings at 15 and 35 DATs, application of pre-emergence herbicide Commit, application of early post-emergence herbicide Pediplus, application of pre-emergence herbicide Commit followed by application of early post-emergence herbicide Pediplus, application of pre-emergence herbicide Commit followed by one hand weeding at 35 DAT, and application of early post-emergence herbicide Pediplus followed by one hand weeding at 35 DAT. The experiment was laid out in a split plot design assigning rice cultivars in the main plots and weed management practices in the sub-plots with three replications. Fourteen weed species infested the experimental field belonging to six families. Among the weed species, four were grasses, four were broad leaves and six were sedges. Cultivar exerted significant effect on weed density and dry weight. Both the highest weed density and dry weight were found in BRRI dhan28 and the lowest ones were observed in BRRI dhan29 rice cultivar. Weed density and weed dry weight were significantly influenced by weeding regime. The highest weed density and dry weight were observed in no weeding condition and application of pre-emergence herbicide Commit followed by one hand weeding at 35 DAT showed the best performance. BRRI dhan29 produced the highest grain and straw yields among the cultivars. Weed control had pronounced influence on yield of rice. The highest grain yield was obtained in application of pre-emergence herbicide Pretilachlor (Commit)followed by one hand weeding at 35 DAT and the lowest one was obtained in control (no weeding) treatment. From the results of the study it may be concluded that rice cultivar BRRI dhan29 with application of pre-emergence herbicide Commit followed by one hand weeding at 35 DAT might be the best treatment for controlling weed effectively as well as obtaining highest yield and highest economic return.J Bangladesh Agril Univ 17(3): 265–273, 2019